INSURANCE COMPANIES' LEGAL OBLIGATIONS FOR ACTS OF DEFAULT RELATED TO CONSUMER PROTECTION - Siregar, Dahris (jfpublisher, 2025)
A company that can handle all the risks that its clients face is the insurance business. Once the parties have achieved their respective goals, the insurance agreement can be successfully executed. One of the defaulting parties causes the agreement not to be effectively executed. However, what if the insurance provider defaults and violates the contract with the policyholder. The problem of this research is how to hold insurance companies legally accountable for their defaults and the types of settlements reached in the event of a dispute. Finding out how policyholders are legally protected against insurance company defaults is the aim of this study. This study uses a normative juridical approach. Based on the results of the study, the insurance company's default is legally responsible for fulfilling its obligations to policyholders who suffer losses in terms of filing claims, where the obligation of the insurance policyholder's customer is to pay premiums and the policyholder's customer's right is to receive compensation in the event of a claim. There are two ways to settle an insurance dispute: in court and out of court. Through the court, if the insurance dispute does not find a common ground between the insurer and the insured, out-of-court dispute resolution can be pursued through the BMAI dispute resolution institution through mediation, adjudication, and arbitration. Legal protection for policyholder customers by having authentic evidence, namely the policy.